2016
DOI: 10.1002/pssa.201600360
|View full text |Cite
|
Sign up to set email alerts
|

Permanent annihilation of thermally activated defects which limit the lifetime of float‐zone silicon

Abstract: (2016) Permanent annihilation of thermally activated defects which limit the lifetime of float-zone silicon. Physica Status Solidi A . Permanent WRAP URL:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 18 publications
6
78
0
Order By: Relevance
“…After removal of the phosphosilicate glass in buffered HF and subsequent SC cleaning, the wafers were thermally oxidized in oxygen (with background dichloroethylene) for 60 min at 1050°C. The oxidation annihilates grown-in defects [35], [36] while the phosphorus diffusion getters impurities and prevents external contamination during the high-temperature oxidation. Following the high-temperature processing, the SiO 2 film and phosphorus diffused region were chemically etched away.…”
Section: Quantifying Surface Recombination Of Superacid-treated Simentioning
confidence: 99%
“…After removal of the phosphosilicate glass in buffered HF and subsequent SC cleaning, the wafers were thermally oxidized in oxygen (with background dichloroethylene) for 60 min at 1050°C. The oxidation annihilates grown-in defects [35], [36] while the phosphorus diffusion getters impurities and prevents external contamination during the high-temperature oxidation. Following the high-temperature processing, the SiO 2 film and phosphorus diffused region were chemically etched away.…”
Section: Quantifying Surface Recombination Of Superacid-treated Simentioning
confidence: 99%
“…Lower temperature (≈250 to 450 °C) processes to deposit dielectric films can impact on the bulk lifetime in at least three ways. Firstly, annealing can activate bulk recombination centres − even in high purity float‐zone silicon …”
Section: Motivation For Temporary Passivationmentioning
confidence: 99%
“…The explanation suggested that the defect that becomes activated originates from the growth conditions of the ingot and results in a reduction in the bulk lifetime. According to a previous study, further temperature annealing at higher temperatures (from 800 to 1100 °C) should provide complete recovery of the charge carrier lifetime in FZ silicon.…”
Section: Resultsmentioning
confidence: 91%